Carotenoid and peptide supplementation from Caulerpa sp. (sea grapes) extract mitigate metabolic syndrome in cholesterol-enriched diet rats via modulation of gut microbiota - Rudy Kurniawan; Fahrul Nurkolis; Agussalim Bukhari; Andi Yasmin Syauki; Burhanudin Bahar; Andi Makbul Aman; Nurpudji Astuti Taslim (Diabetology & Metabolic Syndrome)
Abstract Background Metabolic syndrome (MetS) is a multifactorial disorder characterized by obesity, dyslipidemia, insulin resistance, and hypertension, increasing the risk of cardiovascular diseases and type 2 diabetes mellitus (T2DM). Recent evidence suggests that gut microbiome dysbiosis plays a significant role in MetS pathogenesis. Functional foods enriched with bioactive compounds, particularly those derived from marine sources, have emerged as promising interventions. Objective This study aimed to evaluate the effects of carotenoid and peptide supplementation from Caulerpa sp. (sea grapes) extract on metabolic syndrome and gut microbiome modulation in cholesterol-fat-enriched diet (CFED) rats. Methods A randomized preclinical trial was conducted using CFED-fed rats, supplemented with carotenoid and peptide extracts from Caulerpa sp. Metabolic parameters, lipid profiles, enzymatic activities, and inflammatory biomarkers were assessed. Additionally, gut microbiota composition was analyzed using high-throughput sequencing techniques. Results Supplementation with Caulerpa sp. extracts significantly improved metabolic markers, including reductions in body weight gain, triglycerides, total cholesterol, low-density lipoprotein (LDL), and blood glucose levels, while increasing high-density lipoprotein (HDL) (p < 0.05). Enzymatic analysis revealed suppression of key metabolic enzymes, such as α-glucosidase and lipase, suggesting potential regulatory effects on lipid and carbohydrate metabolism. Moreover, gut microbiome analysis indicated increased microbial diversity and favorable shifts in bacterial taxa. Specifically, Faecalibacterium and Lactobacillus, known for their anti-inflammatory and metabolic benefits, were enriched, while Oscillospira, which has been associated with metabolic disorders, showed a decline. These microbial changes suggest a potential role of Caulerpa sp. in modulating gut health and systemic metabolism. Conclusion The findings demonstrate that carotenoid and peptide extracts from Caulerpa sp. effectively mitigate metabolic syndrome through metabolic regulation, gut microbiome modulation, and anti-inflammatory mechanisms. This study highlights Caulerpa sp. as a potential functional food for MetS management, paving the way for future clinical applications. Clinical trial number Not applicable. Graphical Abstract